2001
DOI: 10.1038/sj.bmt.1703052
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring vital signs in a bone marrow transplant unit: are they needed in the middle of the night?

Abstract: Summary:Monitoring vital signs (VS) is a routine procedure in bone marrow transplant (BMT) units, but such monitoring can interfere with sleep. We hypothesized that middle of the night (MON) monitoring may not be needed in all patients. Charts of 20 consecutive patients who underwent BMT were reviewed for MON monitoring to determine the frequency with which monitoring resulted in a nursing intervention, call to the physician or change in treatment by the physician. Charts were also reviewed for day time events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
(10 reference statements)
0
9
0
1
Order By: Relevance
“…Environmental interventions to improve sleep among inpatients may be more effective than patient-based interventions (e.g., minimizing of nighttime vital signs monitoring). A study conducted by Sharda and colleagues suggests that the vital sign monitoring might not be necessary for HCT patients with low-risk profiles (i.e., lack of daytime fever and CNS complaints) and may lead to improved sleep and health (73). In contrast, use of an hypnotic (zolpidem) has been associated with increased inpatient falls (74).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental interventions to improve sleep among inpatients may be more effective than patient-based interventions (e.g., minimizing of nighttime vital signs monitoring). A study conducted by Sharda and colleagues suggests that the vital sign monitoring might not be necessary for HCT patients with low-risk profiles (i.e., lack of daytime fever and CNS complaints) and may lead to improved sleep and health (73). In contrast, use of an hypnotic (zolpidem) has been associated with increased inpatient falls (74).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted at the University of Florida, Sharda et al. reviewed the effects of monitoring vital signs in a bone marrow transplant unit and concluded that, although frequent vital sign monitoring is presumed to be required for the safe management of transplant patients, the benefits thereof did not outweigh the detriments of sleep deprivation 15 . Specifically, sleep promotes growth hormone production, 16 which improves healing, 17 whereas sleep deprivation interferes with the immune system, 18–20 glucose metabolism, 21 cortisol and catecholamine levels 22–24 and decreases pain tolerance 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Sharda and associates reviewed the effects of monitoring of vital signs in a bone marrow transplant unit and concluded that although frequent vital sign monitoring is presumed to be required for the safe treatment of transplant patients, the benefits thereof did not outweigh the detriments of sleep deprivation (11). Specifically, sleep promotes increases growth hormone production (12), which improves healing (13), whereas sleep deprivation interferes with the functioning of the immune system (14-16); glucose metabolism (17); cortisol and catecholamine (18)(19)(20) levels; and decreases pain tolerance (21,22).…”
Section: Discussionmentioning
confidence: 99%